Los simuladores virtuales para el aprendizaje de Química General con los estudiantes de segundo semestre de la carrera de Pedagogía de las Ciencias Experimentales Química y Biología en el periodo mayo-octubre 2021 - Sagñay Colcha, Deysi del Pilar (2022)
Nowadays in several Latin American countries, education is destined to develop a process of significant changes in the use of new technologies. This research is based on: ¿How does the use of virtual simulators contribute to the teaching-learning process of the subject of General Chemistry? The objective of the research was to propose virtual simulators to help the learning of General Chemistry. The research methodology was non-experimental, diagnostic, descriptive, bibliographic and field type, its type of study was cross-sectional; the analysis-synthesis, inductive and deductive methods were used. For data collection, a survey was applied to 43 students of the second semester of the career of Pedagogy of Experimental Sciences Chemistry and Biology through a questionnaire as an instrument, applied to students that made up of 10 questions with multiple options. When performing the analysis of the data, it was possible to show that the learners agree to use the virtual simulators for support the experiential learning and feedback. It was concluded that virtual simulators strengthen the learning of General Chemistry, being the most significant: Chemlab Simulator, Crocodile Chemistry and PhET Simulator as they help to a greater ease of learning and motivate the student to promote the development of new knowledge. Therefore, it is recommended to promote the use of other virtual simulators for the help of learning General Chemistry.